2020
DOI: 10.3389/fncel.2020.593027
|View full text |Cite
|
Sign up to set email alerts
|

Brain Temperature Alters Contributions of Excitatory and Inhibitory Inputs to Evoked Field Potentials in the Rat Frontal Cortex

Abstract: Changes in brain temperature have been reported to affect various brain functions. However, little is known about the effects of temperature on the neural activity at the network level, where multiple inputs are integrated. In this study, we recorded cortical evoked potentials while altering the local brain temperature in anesthetized rats. We delivered electrical stimulations to the midbrain dopamine area and measured the evoked potentials in the frontal cortex, the temperature of which was locally altered us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…The validity of our findings should be tested in conditions where the body temperature measurements are carefully controlled and/or using core body temperature in future studies. Moreover, previous findings have shown that behavioral characteristics specific to ASD were moderated in children with clinical ASD diagnosis during a fever 17 and that the decrement in cortical temperature increases brain activity [10][11][12][13][14][15] and weakens the contribution of inhibitory inputs to neural activities relative to excitatory inputs 15 . It may be possible that the magnitudes of characteristics specific to autistic traits fluctuate over time at a daily level with changes in body temperature with circadian rhythm 25 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The validity of our findings should be tested in conditions where the body temperature measurements are carefully controlled and/or using core body temperature in future studies. Moreover, previous findings have shown that behavioral characteristics specific to ASD were moderated in children with clinical ASD diagnosis during a fever 17 and that the decrement in cortical temperature increases brain activity [10][11][12][13][14][15] and weakens the contribution of inhibitory inputs to neural activities relative to excitatory inputs 15 . It may be possible that the magnitudes of characteristics specific to autistic traits fluctuate over time at a daily level with changes in body temperature with circadian rhythm 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Notably, neurophysiological evidence shows that, in some brain areas, brain activity increases as cortical temperature decreases 10 15 . Pharmacological evidence further suggests that a decrease in cortical temperature weakens the contribution of inhibitory inputs to neural activity relative to excitatory inputs 15 . These findings lead to an assumption that lower brain temperature is associated with higher autistic traits because of the excitatory-dominant neuronal activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those situations, gradual cooling effectively avoided seizure induction. The mechanism behind this is unknown as cooling is wellestablished to suppress seizures 45 but may be due to inhibition of GABA circuits that can be corrected with medication 46 . Other adverse effects of hypothermia are possible via reduced neural firing and cellular swelling but may be solved by gradually adjusting temperature, intermittent hypothermia, administering molecular inhibitors [30][31][32] , and the use of adjuvants to reduce the total length of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature can have profound effects on the central nervous system (CNS) ( Bracho and Orkand, 1972 ; Weight and Erulkar, 1976 ; Pyott and Rosenmund, 2002 ; Volgushev et al, 2004 ; Micheva and Smith, 2005 ; Young et al, 2006 ; Kim and Connors, 2012 ), especially on the neuronal synapse. At the level of the synapse, temperature rapidly affects neurotransmitter release ( Weight and Erulkar, 1976 ; Pyott and Rosenmund, 2002 ), synaptic vesicle (SV) cycling ( Micheva and Smith, 2005 ; Kushmerick et al, 2006 ), neuronal excitability ( Young et al, 2006 ; de la Peña et al, 2012 ; Hook, 2020 ), receptor kinetics ( Mokrushin et al, 2014 ; Gotoh et al, 2020 ), and short-term synaptic plasticity ( Klyachko and Stevens, 2006 ). In the longer term, low temperature (hypothermia) is generally associated with synaptic disassembly ( Popov and Bocharova, 1992 ; Magariños et al, 2006 ; von der Ohe et al, 2006 , 2007 ; Peretti et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%